Yeasts of Burden: Exploring the Mycobiome–Bacteriome of the Piglet GI Tract - Arfken, Ann M.; Frey, Juli Foster; Ramsay, Timothy G.; Summers, Katie Lynn (Frontiers in Microbiology, 2019)
Interactions between the bacteria and fungi in the gut microbiome can result in altered nutrition, pathogenicity of infection, and host development, making them a crucial component in host health. Associations between the mycobiome and bacteriome in the piglet gut, in the context of weaning, remain unknown. Weaning is a time of significant stress, dietary changes, microbial alterations, and a predisposition to infection. The loss of animal health and growth makes potential microbial interventions of interest to the swine industry. Recent studies have demonstrated the diversity and development of the microbiome in the gastrointestinal tract of piglets during weaning, resulting from the dietary and physiological changes. Despite these advances, the role of the mycobiota in piglet health and its contribution to overall microbiome development remains mostly unknown. In this study we investigated the bacteriome and the mycobiome after weaning in the gastrointestinal tract organs and feces from 35-day old piglets. Following weaning, the α-diversity and amplicon sequence variants (ASV) counts of the bacteriome increased, proximally to distally, from the stomach to the feces along the GI tract, while the mycobiome α-diversity and ASV counts were highest in the porcine stomach. β-diversity analyses show distinct clusters based on organ type in the bacteriome and mycobiome, but dispersion remained relatively constant in the mycobiome between organ/fecal sites. Bacteroidetes, Firmicutes, and Epsilonbacteraeota were the most abundant bacterial phyla present in the GI tract and feces based on mean taxonomic composition with high variation of composition found in the stomach. In the mycobiome, the dominant phyla were Ascomycota and Basidiomycota, and the stomach mycobiome did not demonstrate the same high level of variation observed in the bacteriome. Potential interactions between genera were found in the lower piglet GI bacteriome and mycobiome with positive correlations found between the fungus, Kazachstania, and several bacterial species, including Lactobacillus. Aspergillus demonstrated negative correlations with the short chain fatty acid-producing bacteria Butyricoccus, Subdoligranulum, and Fusicatenibacter. This study demonstrates the distinct colonization dynamics between fungi and bacteria in the gastrointestinal tract and feces of piglets directly following weaning and the potential interactions of these microbes in the porcine gut ecosystem.